Modulatory effects of guava extract on adriamycin (doxorubicin) induced toxicity in wistar rats (2016)
Adriamycin, though, a drug of choice in cancer therapy, its use is associated with acute and chronic complications, which are capable of exacerbating the conditions of the patients. Thus, efforts are being directed at evaluating several compounds, antioxidants and natural products that are capable of ameliorating these complications whilst still retaining the potency and efficacy of Adriamycin as an anti cancer agent. The modulatory and ameliorative effects of methanol guava leaf extract (Psidium guajava Linn) against Adriamycin/Doxorubicin toxicity was evaluated in Wistar rats. Adriamycin (ADR) injection resulted in considerable liver and kidney damage as seen in the form of elevated liver enzymes, total protein as well as urea and creatinine levels in the blood. It also resulted in increases in the total triglyceride and cholesterol levels. The use of the extract alone on the other hand showed hepatoprotective and nephroprotective properties of guava leaf extract in that the above parameters were significantly lower than those of the untreated control. The protective effect of the extract against ADR toxicity was however limited to the liver. Effects which, may be due to the antioxidant and free radical scavenging properties of some of the components of the extract.